2019
DOI: 10.1016/j.jcis.2018.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of ellipsoidal particles at fluid-fluid interfaces with an empirical pair potential

Abstract: Colloidal particles adsorbed at fluid-fluid interfaces interact via mechanisms that can be specific to the presence of interfaces, for instance, lateral capillary interactions induced by nonspherical particles. Capillary interactions are highly relevant for self-assembly and the formation of surface microstructures, however, these are very challenging to model due to the multibody nature of capillary interactions. This work pursues a direct comparison between our computational modelling approach and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 68 publications
1
21
2
Order By: Relevance
“…Hence, the clustering of CS-165 is a result of the capillary interactions appearing for anisotropic particles. The main difference between the simulation of Luo et al 40 and the experiment in this study is that the clusters in simulations were not compressed with external barriers within one direction and, as a result, no prominent orientation of these clusters was observed.…”
Section: Analysis Of the Experimentally Obtained Monolayercontrasting
confidence: 60%
See 1 more Smart Citation
“…Hence, the clustering of CS-165 is a result of the capillary interactions appearing for anisotropic particles. The main difference between the simulation of Luo et al 40 and the experiment in this study is that the clusters in simulations were not compressed with external barriers within one direction and, as a result, no prominent orientation of these clusters was observed.…”
Section: Analysis Of the Experimentally Obtained Monolayercontrasting
confidence: 60%
“…In addition, the phase behavior of anisotropic particles is influenced by their aspect ratio, size, wetting angle and contact line. [38][39][40] For example, the shape of the compression isotherms differentiates when ellipsoids with different aspect ratios are compared. 38 Similar to the spherical case an even more complex behavior for compression isotherms can be envisioned when a microgel shell is added to an anisotropic core.…”
Section: Introductionmentioning
confidence: 99%
“…Similar simulations for large numbers of native globular protein molecules are not yet available because of computational limitations 32 . Recent simulations on interfaces stabilized by ellipsoidal colloidal particles, interacting through capillary interactions 33 , do however show similar types of heterogeneous structures, varying from randomly aggregated clusters at low surface coverage, to strand-like structures at high surface coverage.
Figure 4Structures formed by block copolymers at the liquid-vapor interface: ( a ) linear strands (effective dimension d e =1), ( b ) in-plane clusters (1≤ d e ≤2), ( c ) 3d clusters (2≤ d e ≤3), and ( d ) 3d films ( d e =3). The top row shows the side view and the bottom row shows the top view of the interfacial film.
…”
Section: Resultsmentioning
confidence: 99%
“…In case of nanopore-confined colloids, these deviations are especially significant when the size of the suspended particles or macromolecules is comparable to the size of the hosting nanopore. Experimental [1][2][3][4][5] , theoretical [6][7][8][9][10][11] and simulation [12][13][14][15][16][17][18][19][20][21] studies on confined colloidal suspensions have shown the existence of a rich realm of nanostructures that are not observed in the bulk. Additionally, depending on the adhesive interactions established between the fluid and the pore walls and their relevance with respect to the cohesive interactions between fluid particles, several new phenomena, such as wetting, capillary condensation and evaporation, layering, anchoring, are detected [22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%